Determinasi Nilai Perusahaan pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Rizky Fillhayati (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2020)
The purpose of this study is to analyze the effect of firm size and debt to equity ratio on firm value with profitability as an intervening variable. This research is a causality study on consumer goods industry companies listed on the Indonesia Stock Exchange in 2014 - 2017. The number of samples is 34 companies from a total population of 36 companies with purposive sampling technique. Data analysis uses path analysis.The results show that firm size affects the firm value. Debt to equity ratio affects the firm value. Profitability affects the firm value.